PERKEMBANGAN SANGGAR TARI WARINI PADA SAAT PANDEMI COVID-19 - Kadek Ayu Mira Subandi; I.A Wimba Ruspawati; I Wayan Budiarsa (Jurnal IGEL : Journal Of Dance, 2023)
Sanggar Warini is one of the famous studios in Denpasar City, formed on March 15, 1973, chaired by Ni Ketut Arini, SST which is located on Jl. Kecubung Gang Soka No. 1, Banjar Lebah, Sumerta Kaja Village, East Denpasar. Sanggar Warini has been in the art world for a long time. This studio is engaged in the arts, especially dance. This studio is a place for children's creativity to develop, and this studio and Ms. Arini have produced many young generations who will develop and preserve art. and culture in Bali, besides that many works of art have been born from the Sanggar Warini. Sanggar Warini has hundreds of students consisting of girls and boys. This studio has developed to date, but in the last 2 years there have been obstacles due to the Covid-19 Pandemic which is not allowed to carry out activities that trigger crowds. Keywords: Sanggar Warini, Covid-19, Development, Dance Art